Terahertz modulation of the Cotton-Mouton effect. (November 2019) - Barsaume, S; Mashkovich, E A; Grishunin, K A; Telegin, A V; Sukhorukov, Y P; Christianen, P C M; Rasing, Th; Kimel, A V
Abstract: The ultrafast dynamics of the magneto-optical response triggered in the ferromagnetic semiconductor CdCr2Se4 by an intense nearly single cycle THz pulse is investigated. The dependence on the strength and the polarity of the external magnetic field, and the polarization of the THz pulse can be explained by a phenomenological expression that attributes the observed dynamics to the Cotton-Mouton effect at THz frequencies.